Investigation on Probable Trigger Mechanism of Landslide - F.R.Razdean, Adri Danial (IRC, 2019)
Landslide has been one of the natural or man made disaster that cause many lives at risk. Occurrence of landslide in general has been known to be either in s a small scale or massive scale. Despite the scale of the destruction, these do matter especially to the public awareness. However, special care is to be taken care by forensic geotechnical engineers on determination on the probable trigger mechanism of landslide. Therefore, they must develop a framework to investigate on the said matter. The important factors that need to be included are crucial in the investigation process. Said factor can be trigger factor of landslide, mechanism of landslide and also the type of landslide. These factors contribute much on the disastrous impact of landslide. Therefore, these matter need to be discuss further in order aid in the process of identification of landslide and in the future, may help in reducing or preventing the occurrence of landslide from happening more often.